macroecology of phylogenetically structured hummingbird–plant networks - Martín González, Ana M; Dalsgaard, Bo; Nogués‐Bravo, David; Graham, Catherine H; Schleuning, Matthias; Maruyama, Pietro K; Abrahamczyk, Stefan; Alarcón, Ruben; Araujo, Andréa C; Araújo, Francielle P; Azevedo, Severino Mendes, Jr; Baquero, Andrea C; et al. (Global ecology and biogeography, 2015)
AIM: To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. LOCATION: Fifty‐four communities along a c. 10,000 km latitudinal gradient across the Americas (39° N–32° S), ranging from sea level to c. 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. METHODS: We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). RESULTS: Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny (R² = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors (R² = 0.20–0.44 and R² = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. MAIN CONCLUSIONS: Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.